PERAMALAN CURAH HUJAN DI BANDARA INTERNASIONAL I GUSTI NGURAH RAI MENGGUNAKAN METODE FUNGSI TRANSFER - AULIA, NURATUL; SUMARJAYA, I WAYAN; SRINADI, I GUSTI AYU MADE (E-Jurnal Matematika; Vol 12 No 3 (2023)DO - 10.24843/MTK.2023.v12.i03.p421, 2023)
The aim of this study was to identify the model and outcomes of the rainfall forecast at I Gusti Ngurah Rai International Airport using a transfer function model. The outcomes of the rainfall forecast at I Gusti Ngurah Rai International Airport are displayed using regression analysis based on the influence of the input variable humidity. Numerous characteristics of ARIMA models are included in a forecasting model known as the transfer function model. the best model in predicting rainfall data is   and the level of accuracy of the rainfall forecast results obtained by MAPE value of 26.83%. This shows that the prediction of rainfall in this study is feasible.